2019
DOI: 10.1002/gps.5048
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines or related drugs and risk of pneumonia: A systematic review and meta‐analysis

Abstract: Objective Benzodiazepines and benzodiazepine‐related drugs (BZRDs) are used to treat various psychiatric diseases. However, there are concerns that BZRDs increase the risk of pneumonia. Methods We performed a systematic review and meta‐analysis of observational studies to determine whether BZRD use affects the risk of pneumonia. Our analysis included all observational studies that compared pneumonia development among patients receiving BZRD vs those with no treatment. Results In total, 12 citations of 10 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…The association between psychotropic drugs and pneumonia in older adults varies between drug groups, and some individual drugs, with the majority of research focusing on antipsychotics and BZDs. Systematic reviews and metaanalyses found increased risk of pneumonia associated with antipsychotic [121] and BZD [126] use, but were not specifically focused on the older adult population. Recent studies focusing on the older and potentially more vulnerable population have supported the findings of these systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between psychotropic drugs and pneumonia in older adults varies between drug groups, and some individual drugs, with the majority of research focusing on antipsychotics and BZDs. Systematic reviews and metaanalyses found increased risk of pneumonia associated with antipsychotic [121] and BZD [126] use, but were not specifically focused on the older adult population. Recent studies focusing on the older and potentially more vulnerable population have supported the findings of these systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Dzahini et al [121] calculated the number needed to harm to be 86 in persons aged 65 years or older based on an incidence of community-acquired pneumonia (CAP) in a study from Spain [162]. Sun et al [126] found a small increase in risk of pneumonia with BZD or BZRD use in their metaanalysis, but the impact on a population level of BZD-or BZRD-associated pneumonia may be substantial given the large number of users. To better treat and reduce adverse drug events, including pneumonia, in this growing older population, prescribers need to be informed of the risk of psychotropic drug use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations